2000
DOI: 10.1046/j.1468-2982.2000.00078.x
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Anti-Migraine Compound SB-220453 does not Contract Human Isolated Blood Vessels or Myocardium; A Comparison with Sumatriptan

Abstract: The mechanistically novel benzopyran derivative SB-220453, which is undergoing clinical evaluation in migraine, exhibits a high affinity for a selective, but not yet characterized, binding site in the human brain. It inhibits nitric oxide release and cerebral vasodilatation following cortical spreading depression as well as carotid vasodilatation induced by trigeminal nerve stimulation in the cat. The aim of our study was to investigate the contractile properties of SB-220453 on a number of human isolated bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 31 publications
(39 reference statements)
1
18
0
Order By: Relevance
“…In a further work using the same anaesthetized cat model, tonabersat produces a marked dose-dependent inhibition of repetitive CSD and reduces CSD-induced repetitive episodes of pial artery vasodilatation (Smith et al, 2000). When compared with the serotoninergic agonist sumatriptan (5-HT 1D,1B agonist), tonabersat seemed to be devoid of adverse cardiovascular side-effects in isolated human tissues (MaassenVanDenBrink et al, 2000). In a study using repetitive diffusion-weighted MR imaging, the inhibitory effects of tonabersat on CSD event number and duration of activity was confirmed in vivo in the cat cerebral cortex.…”
Section: Gap Junction Channels As Therapeutic Targetsmentioning
confidence: 99%
“…In a further work using the same anaesthetized cat model, tonabersat produces a marked dose-dependent inhibition of repetitive CSD and reduces CSD-induced repetitive episodes of pial artery vasodilatation (Smith et al, 2000). When compared with the serotoninergic agonist sumatriptan (5-HT 1D,1B agonist), tonabersat seemed to be devoid of adverse cardiovascular side-effects in isolated human tissues (MaassenVanDenBrink et al, 2000). In a study using repetitive diffusion-weighted MR imaging, the inhibitory effects of tonabersat on CSD event number and duration of activity was confirmed in vivo in the cat cerebral cortex.…”
Section: Gap Junction Channels As Therapeutic Targetsmentioning
confidence: 99%
“…It seems to have no contractile effect on isolated vessels or myocardium [54], but it inhibits trigeminally mediated parasympathetic reflexes on carotid vasculature [55]. A RCDBT [56] on glyceryl-trinitrate (GTN)-induced migraine attacks in migraine patients gave inconclusive results, but the study had to be terminated due to side effects, possibly from the interaction of GTN and the study drug.…”
Section: Anticonvulsantsmentioning
confidence: 99%
“…In vitro studies using isolated coronary arteries have shown that 5-HT receptor agonists produce similar activate peripheral 5-HT 1D -receptors located on trigeminal nerve terminals surrounding blood vessels within the effects in endothelium-denuded arterial segments obtained from diseased hearts [15] and in endothelium intact dura mater [11]. The EC 50 at recombinant human 5-HT 1D -receptors is approximately 8 nm for both drugs segments obtained from donor (normal) hearts [19]. However, it is possible that the in vivo situation may be [23]).…”
Section: Analysis Of Data Preparation Of Arterial Segmentsmentioning
confidence: 99%